HISTORICAL ROOTS OF THREE INTELLECTUAL MOVEMENTS - Abu Shanab, Robert E. (مجلة كلية الاداب, 1975)
The primary objective of this paper is to exhibit the historical interrelationships among Logical Positivism, Opera tionalism, and Behaviorism. Although these three movements occurred almost independently of each other, yet, to use S.S. Stevens' words, “ a general community of spirit among them led directly to extensive cross-fertilization ” (1) Specifically, I shall however concern myself as much with the salient points of encounter among these three movements as it is also with (1) a clarification of the historical influence of these movements, and (2) asking some philosophical questions about the result of this influence. But before a discussion of the historical perspective of each movement is delineated, it would behoove us to indicate in a concise manner the general lines of thought concerning each movement.